A-site Ba-deficiency layered perovskite EuBa1−xCo2O6−δ cathodes for intermediate-temperature solid oxide fuel cells: Electrochemical properties and oxygen reduction reaction kinetics. (21st September 2017) - Li, Shuli; Xia, Tian; Li, Qiang; Sun, Liping; Huo, Lihua; Zhao, Hui
Abstract: A-site Ba-deficiency layered perovskite oxides, EuBa1− x Co2 O6− δ (EB1− x CO, x = 0.02 and 0.04), have been synthesized by a citric acid-ethylene diamine tetraacetic acid complexation sol-gel method, and evaluated as potential cathode materials for intermediate-temperature solid oxide fuel cells (IT-SOFCs). Room temperature powder X-ray diffraction patterns indicate that the EB1− x CO oxides crystallize in an orthorhombic symmetry with space group Pmmm . Among all of components, EB0.98 CO exhibits a good chemical compatibility with Ce0.9 Gd0.1 O1.95 (CGO) electrolyte, as evidenced by phase analysis of mixed EB0.98 CO-CGO after calcining at 950 °C for 12 h in air. Thermal expansion analysis gives an average thermal expansion coefficient of 16.7 × 10 −6 K −1 for EB0.98 CO. Thermogravimetric measurement confirms the high oxygen nonstoichiometric characteristic of EB0.98 CO at elevated temperatures. The electrical conductivity values of EB0.98 CO exceed 300 S cm −1 in the temperature range of 100–750 °C. When tested as cathode in IT-SOFCs, the polarization resistance of 0.107 Ω cm 2 and the overpotential of 10 mV at current density of 77 mA cm −2 are achieved in the EB0.98 CO cathode at 700 °C in air. The EB0.98 CO cathode-based anode-supported single cell delivers the maximum power density of 505 mW cm −2 at 700 °C. Finally the rate-limiting steps for oxygen reduction reaction at the EB0.98 CO cathode interface are determined to be the charge transfer reaction and gas-phase diffusion process. Graphical abstract: Highlights: EB0.98 CO has an average TEC value of 16.7 × 10 −6 K −1 at 50–800 °C. EB0.98 CO cathode gives the low ASR of 0.107 Ω cm 2 at 700 °C. EB0.98 CO-based fuel cell delivers a peak power density of 505 mW cm −2 at 700 °C. Rate-limiting steps for ORR at cathode/electrolyte interface are determined.